Effect of oil gland removal at three different ages on the productive performance of broiler chickens. (Comprehensive Journal of Science, 2026)
This experiment was conducted to determine the effect of surgical removal of the oil gland at 10, 15, and 20 days of age on the productive performance of broiler chickens for the following traits: final body weight (42 days), total weight gain, cumulative feed consumption, feed conversion ratio, mortality rate, dressing percentage, recovery rate, productivity per square meter, and production index at the end of the experimental period. One hundred and twenty on day old Ross 308 broiler chickens were used in the study. They were randomly divided into four treatments, with 30 birds per treatment and 10 birds per replicate. The first treatment (T1), the control, was left without the oil gland removal. the oil gland was surgically removed in the second treatment (T2) at 10 days of age, the third treatment (T3) at 15 days of age, and the fourth treatment (T4) at 20 days of age, respectively. The results for the productive traits, including average bird weight at 42 days of age, average cumulative weight gain, feed conversion ratio, production per square meter of chickens, dressing percentage, recovery percentage, and production index, showed a significant advantage for the birds in the treatments (T2) surgical removal of the oil gland at 10 days, (T3) surgical removal of the oil gland at 15 days, and (T4) surgical removal of the oil gland at 15 days, at a level of P
Keywords: Oil gland - Production performance - Broiler chickens